The Russian military : power and policy - Miller, Steven E.; Trenin, Dmitriĭ (American Academy studies in global security., 2004)
Russian military capacity remains a major consideration for global security even in the post-Soviet era. This book assesses today's Russian military and analyzes its possible future direction. The contributors--experts on the subject from both Russia and the West--consider not only how Russia has built its military capacity but also the policies and doctrines that have shaped Russia's defense posture. They discuss such topics as the downsizing of the Russian military, Russia's use of military power in regional conflicts, and the management of Russia's nuclear weapons. For more than a decade, Russian leaders have struggled to formulate security and defense policies that protect Russia's borders and project Russia's influence. The contributors to The Russian Military find that the choices Russian leaders have made have been significantly influenced by the military reforms Russia has attempted to implement since the collapse of the Soviet Union. The protracted and intense debate over military reform has been--and will continue to be--decisive in shaping Russian military capacity.